Perlindungan Hukum Bagi Guru dan Wali Murid Smart Kids Wagir dalam Menciptakan Kenyamanan Proses Belajar di PAUD - Debrina Rahmawati; Ismawati, Ismawati (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
A conducive early childhood education environment requires the integration of legal aspects, ethics, and moral communication between teachers and guardians. Understanding related to this needs to be done at KB Smart Kids Wagir, Malang because it has never been done before. This service activity aims to increase the understanding of teachers and student guardians of KB Smart Kids Wagir, Malang regarding legal protection and the importance of ethical and moral communication in supporting the comfort of the learning process in PAUD. The method used in this service is in the form of socialisation which is attended by teachers and student guardians. The socialisation was carried out with lectures and questions and answers which began with a pre test and ended with a post test. The result of this service is an increase in science and technology from the socialisation participants. In addition, teachers and guardians better understand legal protection, legal relations, morality and ethics in the teaching and learning process in PAUD. The implication of this activity is the importance of strengthening legal literacy and ethical communication in building harmonious relationships between teachers and student guardians in PAUD institutions.